Densification and mechanical properties of ZrO2-CaAl4O7 composites obtained by reaction sintering - Bruni, Yesica Lorena (2016)
Composites of the ZrO2-CaO-Al2O3 system exhibit high corrosion resistance and high chemical stability, these being suitable properties for enhanced performance as refractories. In this work composites based on ZrO2-CaAl4O7 (CA2) were developed by reaction sintering of two pure ZrO2 powders with different particle size (d50 = 0.44 μm and d50 = 8 μm) mixed with high-alumina cement. The effects of CaO to ZrO2 molar ratio, particle size of ZrO2 and sintering temperature on densification, c-ZrO2 formation, microstructure and mechanical properties (Vickers hardness, dynamic Young's modulus and compressive strength) were determined. Porosity and mean pore size of composites reduced with decreasing both particle size of ZrO2 and CaO content. The highest compression strength of ∼350 MPa and hardness of 6 GPa corresponded to dense ZrO2-based composite with 15 vol.% CA2 sintered at 1 400°C.